PENGEMBANGAN ALAT PERAGA SEDERHANA PADA MATERI TEKANAN ZAT DAN PENERAPANNYA DI SMP NEGERI 2 BATUDAA KELAS VIII - Nur Solehan, Mahfud; Yunginger, Raghel; S. Payu, Citron (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2022)
The research aims to develop the simple props in the substance pressure topic in class VIII of SMP Negeri 2 Batudaa. The research method used is the development of the development model, namely 4D model (define, design, develop, disseminate). To create good props, the props must meet the following criteria including validity, practicality, and effectiveness. The research finding indicates that: (1) the validity of props achieves a score of 85,93% (very good) for content validity and 86,67% (very good) for construct validity, (2) the practicality of props achieves a score of 89% (very good) reviewed from teacher activity in using the props, and (3) the effectiveness of props achieves a score of 78,11% (good) reviewed from student activity and achieve a completeness score of 83,87% reviewed from learning outcome.